Efficacy and acceptability of pharmacotherapy for comorbid anxiety symptoms in bipolar disorder: A systematic review and meta‐analysis. (15th September 2021) - Cullen, Clare; Kappelmann, Nils; Umer, Madeha; Abdolizadeh, Ali; Husain, Muhammad Omair; Bonato, Sarah; Sharma, Gaurav; Xue, Siqi; Ortiz, Abigail; Kloiber, Stefan M.; Mulsant, Benoit H.; Husain, Muhammad I.
Abstract: Objective: Anxiety symptoms are highly prevalent among individuals with bipolar disorder (BD) but there is little guidance on pharmacotherapy for these symptoms. The objective of this systematic review and meta‐analysis was to evaluate the available evidence for pharmacotherapy of comorbid anxiety symptoms in BD. Methods: Completed randomized clinical trials (RCTs) of medications for BD published prior to December 2020 were identified through a systematic search of MEDLINE, Embase, PsycInfo, Web of Science, clinicaltrials.gov, and the ISRCTN. Data from RCTs measuring anxiety symptoms at baseline and endpoint and all‐cause discontinuation were pooled to compare the efficacy and acceptability of medications with control conditions. Results: Thirty‐seven RCTs met our inclusion criteria; 13 placebo‐controlled RCTs with 2175 participants had sufficient data to be included in the meta‐analysis assessing anxiety symptoms. Compared with placebo, the overall effect size of medications (primarily atypical antipsychotics) on anxiety symptoms was small with a standardized mean difference (SMD) = −0.22 (95% CI: −0.34 to −0.11). Study heterogeneity was low ( I 2  = 26%). The acceptability of these medications was comparable with placebo with odds ratio of discontinuation from all causes = 0.98 (95% CI: 0.91–1.06). Conclusion: There is limited evidence for a small anxiolytic effect and good acceptability of pharmacotherapy (primarily atypical antipsychotics) in the treatment of comorbid anxiety symptoms in BD. These results highlight the need for further research on medications other than atypical antipsychotics.